Intraoral route for excising a large dermoid cyst of the floor of mouth: A discussion: Intraoral route of dermoid cyst of the floor of the mouth - Karmakar, Shilpi; Mishra, Brijesh (Journal of Surgery and Medicine, 2022)
Surgical excision is an effective treatment for a dermoid cyst (DC) of the floor of the mouth (FOM). A dichotomy of opinions exist regarding the appropriate approach to surgical excision. In this study, we discuss our experience with excising a large DC via an intraoral route. An 18-year-old female presented with swelling of the submental region for one year. Under general anesthesia, an incision was conducted in the mucosa of FOM. By removing some contents, the cyst was delivered in toto. While some studies have stressed that the location of origin and size of the DC influence the route of excision, other authors have pointed out that by the time both median genioglossal and geniohyoid cysts become large enough to produce symptoms, both the muscles are splayed out and thus, the cysts are more amenable to excision by intraoral approach. This case highlights a dichotomy of opinion regarding the existing literature and to educate the clinicians about the benefits of the intraoral route of excision.